Influence of Upwelling in the Southern Waters of Java on CO2 Concentration in Kototabang, Agam District West - Martono Martono; Fanny Aditya Putri (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
Absorption of atmospheric CO2 by the sea through two processes, namely solubility pumps and biological pumps. This study aims to determine the effect of upwelling in the southern waters of Java on atmospheric CO2 concentrations in Kototabang. The data used are in situ CO2 concentration, sea surface temperature and chlorophyll-a concentration from 2004-2016. The method used was descriptive analysis. The results showed that upwelling that occurred during JJA-SON caused a decrease in sea surface temperature to 26.8 °C and 27.1 °C respectively, as well as an increase chlorophyll-a concentration to 2.03 mg/m3 and 2.19 mg/m3. In both seasons CO2 concentration in Kototabang dropped to 385.8 ppm and 385.4 ppm. Meanwhile, when there was no upwelling during DJF-MAM, sea surface temperatures rose to 28.8 °C and 29.0 °C, and chlorophyll-a concentration dropped to 0.32 mg/m3 and 0.54 mg/m3. CO2 concentration in DJF and MAM increased to 386.3 ppm and 386.5 ppm. Based on these results it is known that when upwelling occurs, CO2 concentration decrease and vice versa.